Birds in the Garden and How to Attract them - McKenny, Margaret (Book collections on Project MUSE., 1939)
Birds in the Garden and How to Attract them was first published in 1939. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.This reprint of Birds in the Garden is published by the University of Minnesota Press in answer to a widespread demand for a book of this type-a complete and practical guide for nature lovers who want to enjoy the useful and charming companionship of birds around their homes.Lavishly illustrated with 16 full-page color portraits from.